2018
DOI: 10.1038/s41388-018-0592-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated inflammation promotes angiogenesis and breast cancer via angiopoietin-like 4

Abstract: Obesity is a risk factor for breast cancer and also predicts poor clinical outcomes regardless of menopausal status. Contributing to the poor clinical outcomes is the suboptimal efficacy of standard therapies due to dose limiting toxicities and obesity related complications, highlighting the need to develop novel therapeutic approaches for treating obese patients. We recently found that obesity leads to an increase in tumor-infiltrating macrophages with activated NLRC4 inflammasome and increased interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 41 publications
4
81
3
1
Order By: Relevance
“…Consistent with this idea, depletion of macrophages in obese mice resulted in significant decreases in endothelial cells and enhanced tumor necrosis. Within adipose tissue, adipocytes have also been shown to regulate angiogenesis through the secretion of adipokines [43], and adipokine secretion, including leptin, has been implicated in tumor angiogenesis in the context of obesity [44,45]. Although we observed increased tumor cell invasion into surrounding obese adipose tissue, we did not observe elevated numbers of adipocytes within the tumor mass.…”
Section: Discussioncontrasting
confidence: 78%
“…Consistent with this idea, depletion of macrophages in obese mice resulted in significant decreases in endothelial cells and enhanced tumor necrosis. Within adipose tissue, adipocytes have also been shown to regulate angiogenesis through the secretion of adipokines [43], and adipokine secretion, including leptin, has been implicated in tumor angiogenesis in the context of obesity [44,45]. Although we observed increased tumor cell invasion into surrounding obese adipose tissue, we did not observe elevated numbers of adipocytes within the tumor mass.…”
Section: Discussioncontrasting
confidence: 78%
“…Accumulating evidence has revealed that inflammasomes are involved in the pathological processes of different tumors [14,30,31], but the specific molecular mechanisms remained incompletely elucidated. In this study, we identified different expression patterns and prognostic characteristics of IRGs among 10 cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the functions of inflammasomes in tumor, to a certain extent, are determined by the different types of cells and tissues [12][13][14]. However, there is still no systematic molecular profile of inflammasome-related genes (IRGs) across diverse human cancers until now.…”
Section: Introductionmentioning
confidence: 99%
“…Along with cancer progression, hypoxia and undernutrition occur in cancer tissues due to rapid cancer proliferation [42]. Angiopoietin-like protein 4 (ANG-PTL4) is known to be induced by hypoxia and undernutrition [43], and is induced by IL-1β in a manner dependent on NF-κB-and MAPK-activation to promote angiogenesis and progression in breast cancer [44]. In oral cancer, ANGPTL4 enhances the tumorigenesis and poor prognosis based on the clinical tumor tissues [45].…”
Section: Angptl4mentioning
confidence: 99%